Pregnancy-associated leiomyomas: what is new? - Mohsen MA Abdelhafez; Karim AM Ahmed; Win Win Than; Mohd Nazri Mohd Daud; Mohamad Saffree Jeffree; Fairrul MA Kadir; Dg Marshitah Pg Baharuddin; Firdaus Hayati; Nornazirah Azizan; Doreen Sumpat; Aya AM Eldiastey (Journal of South Asian Federation of Obstetrics and Gynaecology, 2024)
Aims: Owing to the continuous debate and dilemma regarding the appropriate approach for managing fibroids with pregnancy, this review aims to synthesize, analyze and build up evidence from the published studies, especially the recent ones, about the changing trends in the last decade regarding the management of uterine fibroids with pregnancy and the feasibility as well as safety of cesarean myomectomy in comparison to the traditional conservative approach of deferring removal of the fibroids 3–6 months post-partum. Materials and methods: This is a review of the literature, and all the co-authors searched for, gathered, and filtered the most recent publications on the subject through PubMed, Medline, Google search, and others. Findings: The prevalence of fibroids with pregnancy ranges between 0.1 and 3.9% however, the true rate may be higher than this presently reported incidence. Discussion: An increasing trend in diagnosing fibroids with pregnancy is currently clearly obvious, mainly due to the concept of delaying child-bearing as well as the steady increase in the rate of cesarean delivery which leads to more incidental findings of asymptomatic fibroids. Conclusions: Uterine fibroids in pregnancy represent a dilemma in both diagnosis and treatment. Ultrasonography remains the main diagnostic modality for fibroids during pregnancy despite its reduced sensitivity and specificity during pregnancy. Treatment of fibroids with pregnancy continues to be a matter of debate and controversy, where traditionally myomectomy used to be deferred until after delivery and maybe after puerperium. At present both caesarean myomectomy and also, myomectomy during pregnancy have places in modern obstetrics. Statement of significance: • The problem regarding the association of fibroids with pregnancy arises mainly from the challenges in both the diagnosis, where ultrasonography has a reduced sensitivity and specificity during pregnancy, as well as the controversy and debate in the treatment strategies of the condition. • The traditional known practice of managing fibroids in association with pregnancy, is to postpone the removal of fibroids until postnatal and even after puerperium to allow a time for uterine involution and shrinkage of the fibroid hence, minimizing the operative time and the associated blood loss with the potential risks of spontaneous miscarriage, placental dysfunction, fetal malpresentations and preterm birth especially with submucous and intramural fibroids. • This article highlighted the newly introduced interventions in the context of the management of fibroids with pregnancy including, techniques to prevent preterm delivery and achieve term birth in case of treatment delay until post-delivery, or the implementation of cesarean myomectomy as well as myomectomy during pregnancy.